2013
DOI: 10.1002/eat.22158
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child concordance in reporting of child eating disorder pathology as assessed by the eating disorder examination

Abstract: Objective: The aim of this study was to examine parent-youth concordance in reporting of eating disorder pathology, as assessed by the Eating Disorder Examination (EDE) in a clinical pediatric sample. Method:The sample comprised 619 parent-youth dyads of youth (8-18 years) presenting for treatment at a specialist eating disorder clinic. A cross-sectional correlational design was used to examine the association between parent and youth symptom reports.Results: On the whole, parent-youth inter-rater agreement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 53 publications
5
28
1
Order By: Relevance
“…DSM‐5 changes, fortunately, increase emphasis on collateral reporting (i.e., parent and teacher) and behavioral observations in assessment. A recent study by our group showed that standardized parent‐informant assessment can detect eating problems less readily apparent by the young person's report, particularly in cases of AN . A future research enquiry would be to evaluate the discriminant validity of the EDE among children with EDs, other mental illnesses, and healthy controls with respect to ED cognitions and to characterize its usefulness and limitations in a younger population.…”
Section: Discussionmentioning
confidence: 99%
“…DSM‐5 changes, fortunately, increase emphasis on collateral reporting (i.e., parent and teacher) and behavioral observations in assessment. A recent study by our group showed that standardized parent‐informant assessment can detect eating problems less readily apparent by the young person's report, particularly in cases of AN . A future research enquiry would be to evaluate the discriminant validity of the EDE among children with EDs, other mental illnesses, and healthy controls with respect to ED cognitions and to characterize its usefulness and limitations in a younger population.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment should involve both children and their families or carers unless this is contraindicated due to safety concerns such as abuse or domestic violence (Mariano et al, 2013). At assessment, every child or adolescent suspected of having anorexia nervosa needs a comprehensive review of psychological and physiological signs and symptoms.…”
Section: Assessmentmentioning
confidence: 99%
“…For example, Mariano et al [11] found acceptable agreement for the presence of behavioural symptoms (e.g. binge eating, self-induced vomiting, and laxative/diuretic misuse), but poor agreement on frequency of behaviours and experience of disordered eating cognitions, with greater severity reported by young people compared to their parents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Salbach-Andrae et al [12] observed poor concordance between parent and adolescent reports, particularly for internalising behaviours. While several studies have observed good concordance for symptoms of AN [11], one study reported less concerns over weight and restraint in child reports (aged 6–12 years) compared to their parents [6], and another study revealed greater concordance for adolescents with BN compared to those with AN-Restrictive subtype [12]. In contrast, youths suffering from BN have been found to report greater severity of cognitions and frequency of behaviours [11], shape concerns and restraint [6] compared to their parents.…”
Section: Introductionmentioning
confidence: 99%